Interest of a new large diffusive gradients in thin films (L-DGT) for organic compounds monitoring: On-field comparison with conventional passive samplers. (15th April 2023) - Martins de Barros, Rachel; Rougerie, Juliette; Guibal, Robin; Lissalde, Sophie; Buzier, Rémy; Simon, Stéphane; Guibaud, Gilles
Abstract: In this work, the performances of a Large Diffusive Gradients in Thin films (L-DGT, i.e., a DGT based on a Chemcatcher® holder with a 5-fold larger sampling area) were compared on-field with the conventional DGT and the Polar Organic Chemical Integrative Sampler (POCIS) for the monitoring of a wide range of organic contaminants ( i.e., 65 pesticides and metabolites, 53 pharmaceuticals and 12 hormones). These three passive samplers were simultaneously deployed in four rivers during 14 days. Their performances were then evaluated according to their detection and quantification capacities and their physical robustness. The results obtained confirm the advantages of the L-DGT over the conventional DGT regarding its sensitivity but also its robustness during field deployment. The POCIS provides the higher sensitivity, allowing the detection of more organic compounds compared to the DGT and, to a lesser extent, the L-DGT. However, both L-DGT and DGT reduces the uncertainty on the determination of the time-weighted average concentrations (CW ), mainly due to the narrow range of variation of their calibration parameters. Indeed, for a given compound, CW can vary up to only a 3-fold factor with DGT and L-DGT compared to a 2 to 10-fold factor (up to 50) with POCIS. Thus, the L-DGT appears to be more suitable than DGT in low-contaminated contexts, which require higher sensitivity, or than POCIS when a CW determination is needed. For a qualitative evaluation however, the POCIS remains the most suitable passive sampler. Graphical abstract: Image 1 Highlights: Performances comparison of POCIS, o-DGT and Large o-DGT in field conditions. Improved performances of o-DGT via Lo-DGT (with a 5-time increased area). Lower Lo-DGT sensitivity but better reliable CW determination than POCIS. Easier determination and more reliable D than RS .